Social Media Marketing Strategy in Increasing Customer Engagement of Taman Safari Ndonesia Bogor (Case Study on Instagram @Taman_Safari) - Jessica Bong Natasha; Chininta Rizka Angelia; Daniel Susilo (PT FORMOSA CENDEKIA GLOBAL, 2023)
With the pandemic condition, Taman Safari Indonesia Bogor is also looking for ways to increase customer engagement. One of the methods used is to carry out a social media marketing strategy with promotions through social media to increase customer engagement. This research was conducted to determine the social media marketing strategy in increasing customer engagement at Taman Safari Indonesia Bogor in the case study of Instagram @taman_safari. The concept used in this research is the social media marketing strategy from Tuten & Solomon (2018) and customer engagement from Cuillierier (2016) and Zyminkowska (2019). This research uses descriptive qualitative research and case study methods. The data collection of the research carried out were interviews and documentation. Interviews were conducted in-depth (in-depth interviews) to research participants. The criteria for participants is to have to work at Taman Safari Indonesia Bogor for a period of more than 1 year. The results of this study indicate that in increasing customer engagement, Instagram @taman_safari has implemented a social media marketing strategy that is structured through specific stages.